Mengatasi pola perilaku pra remaja pasca covid 19 dari sudut pandang pendidikan agama Islam - Sukatin, Sukatin; Maharani. S, Sorta; Mabruroh, Siti Izzatul; Wahyuni, Wahyuni; Ibrahim, Fernando (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Post-covid 19, educational institutions began to change their status from online to offline in accordance with applicable government policies. This study aims to determine the behavioral patterns of pre-adolescents after covid-19 and how to overcome these behavioral patterns from an Islamic religious education perspective. This study is a qualitative descriptive research method using a case study approach. This study collected data using a structured interview method and took samples using convenience sampling techniques. According to the results of the study, the behavioral patterns of pre-adolescents have increased significantly, which are usually difficult to control, becoming increasingly difficult to control to the point of being out of control. The way teachers overcome this problem is by instilling Islamic religious education values in the form of religious, intellectual, moral, psychological and social values. The findings of the researchers show that educators instill these values so that the behavioral patterns of pre-adolescents gradually change. It can be concluded that with Islamic religious education, changes in the behavioral patterns of pre-adolescents after Covid-19 can be overcome.